Computing fairness: ethics of modeling and simulation in public health. (February 2022) - Bak, Marieke AR
The field of public health increasingly utilizes computational models. In this context, computer scientists are confronted with moral dilemmas like those around modeling the distribution of scarce resources. However, there is a lack of research on the ethical implications of computer modeling and simulation (M&S). In this paper I aim to show that taking a transdisciplinary ethical perspective is useful when analyzing these implications. The practice of modeling geospatial distribution of automated external defibrillators for sudden cardiac arrest treatment is used as a case study. It is shown that there exists no consensus on what theory of justice should underlie choices in computer M&S of public health resources, and that professionals struggle with building equity considerations into their models. The example highlights new ethical consequences arising at the nexus of public health and M&S. Computer models and simulations are not morally neutral, but have the effect of making those involved in their creation more responsible for making just choices. For some moral dilemmas, such as those related to distributive justice, there may be no correct solution that can be readily modeled. Promoting professional responsibility through a code of ethics will not help prescribe a right course of action in these situations. I suggest therefore that procedural justice and deliberation with a range of stakeholders is needed to take ethical considerations into account "by design" when developing computer models and simulations for public health policy. Future research should reflect on the content and practical procedures for these deliberations.